Measurement of relative operational efficiency of SOEUs in India using data envelopment analysis. (22nd May 2009) - Meenakumari, R.; Kamaraj, N.; Thakur, Tripta
A nonparametric approach to frontier analysis, data envelopment analysis (DEA) is applied in this work to evaluate the relative operational efficiency of state owned electric utilities (SOEU) in India. Two different models viz CCR model and BCC model are applied to evaluate the overall efficiency and technical efficiency. Twenty nine SOEUs in India are considered for the analysis and the relative operational efficiency scores are calculated. The results indicate that the performance of several SOEUs are sub-optimal, suggesting a potential for significant improvements in the operation so as to improve the overall efficiency. Also sensitivity analysis is carried out to investigate the effect of changes in the solutions of the model.